Future Orientation Training to Enhance Career Decision-Making Self-Efficacy in Vocational High School X Yogyakarta Students: An Experimental Study - Ayu Gigih Rizqia; Femmy Lekahena; Amin Al Adib (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The high unemployment rate among vocational school graduates in Indonesia is partly due to their low confidence in making career-related decisions, as measured by Career Decision-Making Self-Efficacy (CDMSE). This lack of confidence may hinder students’ work readiness, particularly as they prepare for industrial work practice. This study examined the effectiveness of Future Orientation training in improving CDMSE among vocational students. A quasi-experimental design with an untreated control group and pretest-posttest measures was used. The participants were 28 grade 11 students from a Vocational High School in Yogyakarta, selected through purposive sampling, all with low CDMSE scores. The training aimed to strengthen students’ motivational, affective, and cognitive capacities related to exploring career options, future planning, and goal setting. CDMSE was measured using a scale adapted from Betz and Luzzo, validated by Purnama and Ernawati, with acceptable fit indices (Chi-Square p > .05, RMSEA ≤ .08, CFI ≥ .95, SRMR ≤ 0.08). The Wilcoxon Rank Test showed a significant improvement in CDMSE after the training (p < .01), and the Mann-Whitney Test revealed a significant difference between the experimental and control groups (p < .01). These findings support the effectiveness of Future Orientation training in enhancing CDMSE. Similar programs could be integrated into vocational education to improve career readiness and reduce the risk of unemployment. Keywords: future orientation, career decision-making self-efficacy, vocational high school student